2009
DOI: 10.1088/0004-637x/707/1/428
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Large-Scale Poloidal Flux in Black Hole Accretion

Abstract: We report on a global, three-dimensional GRMHD simulation of an accretion torus embedded in a large scale vertical magnetic field orbiting a Schwarzschild black hole. This simulation investigates how a large scale vertical field evolves within a turbulent accretion disk and whether global magnetic field configurations suitable for launching jets and winds can develop. We find that a "coronal mechanism" of magnetic flux motion, which operates largely outside the disk body, dominates global flux evolution. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(239 citation statements)
references
References 41 publications
(54 reference statements)
6
231
1
1
Order By: Relevance
“…Our results can be compared to those of the MHD simulations on accretion disks (e.g., Igumenshchev et al 2003;Beckwith et al 2009;Penna et al 2010;Tchekhovskoy et al 2011;McKinney et al 2012;Narayan et al 2012). The magnetic pressure can dominate over the gas pressure in the inner region of the disk, and it becomes a magnetic arrested disk (Igumenshchev et al 2003).…”
Section: ¢ = ¢mentioning
confidence: 86%
“…Our results can be compared to those of the MHD simulations on accretion disks (e.g., Igumenshchev et al 2003;Beckwith et al 2009;Penna et al 2010;Tchekhovskoy et al 2011;McKinney et al 2012;Narayan et al 2012). The magnetic pressure can dominate over the gas pressure in the inner region of the disk, and it becomes a magnetic arrested disk (Igumenshchev et al 2003).…”
Section: ¢ = ¢mentioning
confidence: 86%
“…The possibility of dragging of these fields by accreting plasma, originally suggested by Bisnovatyi-Kogan & Ruzmaikin (1974), is still debated (Lubow et al 1994;Spruit & Uzdensky 2005;Bisnovatyi-Kogan & Lovelace 2007;Rothstein & Lovelace 2008;Beckwith et al 2009). The radial distribution of the magnetic field line inclination is another question that is related to this lack of a profound model for the magnetic field evolution in accretion disks.…”
Section: Discussionmentioning
confidence: 99%
“…This readily occurs for simulations that begin with a large dipole loop. But simulations by Beckwith et al (2008) found that much weaker funnel fields result from quadrupolar field initial conditions, and no funnel field at all develops for toroidal field initial conditions. A strong jet seems to require a net vertical field in the disk midplane whose sign remains consistent for at least an inner-disk inflow time.…”
Section: Global Simulations -Jet Productionmentioning
confidence: 96%
“…The Maxwell stress showed no dependence on H, but the Reynolds stress at the ISCO did decline with disk thickness. Beckwith et al (2008) found that the initial field topology could influence the stress at the ISCO. In particular, a simulation that began with a purely toroidal initial field barely had any enhanced stress at the ISCO.…”
Section: The Spin Of the Holementioning
confidence: 99%
See 1 more Smart Citation